Cultural Parameters of Xanthomonas cucurbitae Causing Bacterial Leaf Spot of Bottle Gourd and Pumpkin - Kumari, Sujata; Jarial, Kumud; Jarial, R. S.; Jandaik, Savita (International Journal of Bio-resource and Stress Management, 2020)
Bacterial leaf spot caused by Xanthomonas cucurbitae is an important disease of cucurbits leading to huge crop losses especially to bottle gourd, pumpkin and squashes in sub tropical zone of Himachal Pradesh. Cultural parameters like effect of different temperatures, pH levels and nutrient media on the growth of two isolates of X. cucurbitae isolated from bottle gourd and pumpkin were studied under in vitro conditions.Among various temperature regimes (15–35 °C) tested for both the isolates, a temperature range of 25 to 30 oC was observed to be optimum, for bottle gourd (5.35×107 cfu ml-1at 25 oC) and pumpkin (4.15×107 cfu ml-1 at 30 oC) isolates. Out of six pH levels (4.0–9.0) tested to see the effect on bacterial growth, the optimum pH range for maximum growth of the bacteria was observed to be 6.0 to 7.0 for bottle gourd (44.16×107 cfu ml-1at pH 6.0 ) and pumpkin (31.62×107 cfu ml-1 at pH 7.0) isolates. However, no growth of the isolates was recorded at pH 4.0. The bacterium grew best in yeast extract calcium carbonate broth (8.11×107 cfu ml-1 and 10.63×107 cfu ml-1; bottle gourd and pumpkin isolates, respectively), nutrient glucose broth (9.31×cfu ml-1; bottle gourd isolate) and nutrient sodium chloride broth (7.70×107 cfu ml-1and 7.33×107 cfu ml-1; bottle gourd and pumpkin isolates, respectively).